Effects of Enriched Environment on COX-2, Leptin and Eicosanoids in a Mouse Model of Breast Cancer - Nachat-Kappes, Rachida (Public Library of Science, 2012)
Cyclooxygenase-2 (COX-2) and adipokines have been implicated in breast cancer. This study investigated a possible link between COX-2 and adipokines in the development of mammary tumors. A model of environmental enrichment (EE), known to reduce tumor growth was used for a syngeneic murine model of mammary carcinoma. 3-week-old, female C57BL/6 mice were housed in standard environment (SE) or EE cages for 9 weeks and transplanted orthotopically with syngeneic EO771 adenocarcinoma cells into the right inguinal mammary fat pad. EE housing influenced mammary gland development with a decrease in COX-2 expressing cells and enhanced side-branching and advanced development of alveolar structures of the mammary gland. Tumor volume and weight were decreased in EE housed mice and were associated with a reduction in COX-2 and Ki67 levels, and an increase in caspase-3 levels. In tumors of SE mice, high COX-2 expression correlated with enhanced leptin detection. Non-tumor-bearing EE mice showed a significant increase in adiponectin levels but no change in those of leptin, F(2)-isoprostanes, PGF(2α), IL-6, TNF-α, PAI-1, and MCP-1 levels. Both tumor-bearing groups (SE and EE housing) had increased resistin, IL-6, TNF-α, PAI-1 and MCP-1 levels irrespective of the different housing environment demonstrating higher inflammatory response due to the presence of the tumor. This study demonstrates that EE housing influenced normal mammary gland development and inhibited mammary tumor growth resulting in a marked decrease in intratumoral COX-2 activity and an increase in the plasma ratio of adiponectin/leptin levels.